Students’ Learning Motivation: An Experimental Study of the 7E Learning Cycle Instructional Model - Istiqomah, Istiqomah; Syafe’i, Imam; Irawan, Rudy; Baharudin, Baharudin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the effectiveness of the Learning Cycle 7E instructional model in enhancing learners’ motivation in Islamic Religious Education (IRE), specifically on the topic “Emulating the Role of Ulama in Spreading Islamic Teachings in Indonesia” at SMK Negeri 5 Bandar Lampung. The research was conducted in response to the low internal drive of learners, which was associated with lecture-dominated instruction and limited interactive learning media. A quasi-experimental posttest-only control group design was employed, involving two randomly selected classes: one experimental group taught using the Learning Cycle 7E model and one control group taught through conventional methods. The instrument utilized was a validated and reliable motivation questionnaire (α = 0.876). Although Hamzah B. Uno identifies six dimensions of learning motivation, this study focused exclusively on the dimension of learning drive and needs, as it corresponds directly with the objective of analyzing students’ internal impulses and perceived necessity to learn during the application of the 7E model. Restricting the measurement to this single dimension enabled a more precise and in-depth examination of internal motivation. The t-test results revealed a significant difference between the two groups (p < 0.05), demonstrating that the Learning Cycle 7E model effectively increased learners’ motivation, particularly in internal drive and learning needs. The study contributes novelty by implementing the 7E model within vocational-level religious education, offering an innovative and interactive approach to support meaningful and sustainable learning.